2018
DOI: 10.33218/prnano1(2).180724.2
|View full text |Cite
|
Sign up to set email alerts
|

A coming era of precision diagnostics based on nano-assisted mass spectrometry

Abstract: Abbreviations:• SNP single-nucleotide polymorphism • qPCR quantitative real-time polymerase chain reaction • a6A N6-allyladenosine • RT reverse transcriptase • CyTOF mass cytometry by time-of-flight • Pre-DC dendritic cells precursors Abstract Precision diagnostics relies on omic analysis by mass spectrometry to overcome the limitation in accuracy by an individual biomarker, due to the complex nature of diseases. Recent development in nanotechnology markedly enhanced sample treatment and detection efficiency o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 51 publications
(62 reference statements)
0
3
0
Order By: Relevance
“…Recently, novel analytical systems were introduced to detect biomarkers for disease diagnosis. [26][27][28][29][30][31][32] The microfluidic chip is a technology for precise control of microfluidics in submicron structures. [33,34] The use of microfluidic chips can facilitate the accurate control and detection of microfluids in the micro and nanoscale space.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, novel analytical systems were introduced to detect biomarkers for disease diagnosis. [26][27][28][29][30][31][32] The microfluidic chip is a technology for precise control of microfluidics in submicron structures. [33,34] The use of microfluidic chips can facilitate the accurate control and detection of microfluids in the micro and nanoscale space.…”
Section: Introductionmentioning
confidence: 99%
“…The future of nano-diagnostics is marked by expanding capabilities, driven by advancements in nanotechnology and its application in medical diagnostics. A group of researchers discuss the era of precision diagnostics ushered in by nano-assisted mass spectrometry (Qian et al, 2018). This technique overcomes the limitations of accuracy in traditional diagnostic methods, particularly when dealing with complex diseases.…”
Section: Expanding Capabilities: the Future Of Nano-diagnosticsmentioning
confidence: 99%
“…A variety of biosensor platforms based on plasmonic nanomaterials with enhancements such as sensor platforms, molecular detection, and cell receptor analysis show promising outlooks from clinical perspectives. 54 Qian et al reported two independent studies based on a MALDI MS approach using plasmonic nanoshells for in vitro diagnostics of early-stage lung cancer patients and individuals with post-operative brain infections. A clear separation between the healthy and patient groups was achieved by the metabolic fingerprinting of biofluids, such as serum, exosomes and cerebrospinal fluid ( Fig.…”
Section: Maldi Ms and Sers Based Diagnosticsmentioning
confidence: 99%